HLA Associations and Risk of Posttransplant Lymphoproliferative Disorder in a Danish Population-Based Cohort. Issue 7 (August 2015) - Vase, Maja Ølholm; Maksten, Eva Futtrup; Strandhave, Charlotte; Søndergaard, Esben; Bendix, Knud; Hamilton-Dutoit, Stephen; Andersen, Claus; Møller, Michael Boe; Sørensen, Søren Schwartz; Kampmann, Jan; Eiskjær, Hans; Iversen, Martin; et al.
Abstract : Background: Posttransplant lymphoproliferative disorder (PTLD) is a feared complication to organ transplantation, associated with substantial morbidity and inferior survival. Risk factors for PTLD include T cell–depleting induction therapy and primary infection or reactivation of Epstein-Barr virus. Possible associations between certain HLA types and the risk of developing PTLD have been reported by other investigators; however, results are conflicting. Methods: We conducted a retrospective, population-based study on 4295 Danish solid organ transplant patients from the Scandiatransplant database. Having identified 93 PTLD patients in the cohort, we investigated the association of HLA types with PTLD, Epstein-Barr virus status and time to PTLD onset. The outcomes survival and PTLD were evaluated using Cox regression; mismatching, and the PTLD-specific mortality were evaluated in a competing risk analysis. Results: Risk of PTLD was associated with male sex (odds ratio, 1.70; 95% confidence interval, 1.07-2.71), and, in women, HLA-DR13 conferred an increased risk (odds ratio, 3.22; 95% confidence interval, 1.41-7.31). In multivariate analysis, HLA-B45 and HLA-DR13 remained independent predictive factors of PTLD. Mismatching in the B locus was associated with a reduced risk of PTLD ( P < 0.001). Overall survival was poor after a PTLD diagnosis and was significantly worse than that in the remaining transplant cohort ( P < 0.001). Conclusions: Our data indicate risk-modifying HLA associations, which can be clinically useful after transplantation in personalized monitoring schemes. Given the strong linkage disequilibrium in the HLA region, the associations must be interpreted carefully. The large size, virtually complete ascertainment of cases and no loss to follow-up remain important strengths of the study. Abstract : Supplemental digital content is available in the text.